Microstructures of superhydrophobic plant leaves - inspiration for efficient oil spill cleanup materials. (16th August 2016) - Zeiger, Claudia; Rodrigues da Silva, Isabelle C; Mail, Matthias; Kavalenka, Maryna N; Barthlott, Wilhelm; Hölscher, Hendrik
Abstract: The cleanup of accidental oil spills in water is an enormous challenge; conventional oil sorbents absorb large amounts of water in addition to oil and other cleanup methods can cause secondary pollution. In contrast, fresh leaves of the aquatic ferns Salvinia are superhydrophobic and superoleophilic, and can selectively absorb oil while repelling water. These selective wetting properties are optimal for natural oil absorbent applications and bioinspired oil sorbent materials. In this paper we quantify the oil absorption capacity of four Salvinia species with different surface structures, water lettuce ( Pistia stratiotes) and Lotus leaves (Nelumbo nucifera), and compare their absorption capacity to artificial oil sorbents. Interestingly, the oil absorption capacities of Salvinia molesta and Pistia stratiotes leaves are comparable to artificial oil sorbents. Therefore, these pantropical invasive plants, often considered pests, qualify as environmentally friendly materials for oil spill cleanup. Furthermore, we investigated the influence of oil density and viscosity on the oil absorption, and examine how the presence and morphology of trichomes affect the amount of oil absorbed by their surfaces. Specifically, the influence of hair length and shape is analyzed by comparing different hair types ranging from single trichomes of Salvinia cucullata to complex eggbeater-shaped trichomes of Salvinia molesta to establish a basis for improving artificial bioinspired oil absorbents.